O reconhecimento da receita em contratos com clientes com uma abordagem a adoção do CPC 47 (IFRS 15): um estudo comparativo das mudanças das normas em empresas de construção civil e incorporadoras - Fagundes, Vanessa (2017)
With the publication of IFRS 15 and CPC 47 regulations, construction industry will be greatly affected due to the impacts on revenue recognition. Consequently, performance appraisals of this sector, which lacks in-depth studies and greatly affects the country’s economy, may undergo significant changes. Revenue recognition is an essential part of balance sheet analysis and decision-making, once profit is determined from the revenue line in the income statement. Therefore, analyzing the application of CPC 47, a convergence of IFRS 15 and also a milestone in the international accounting evolution as the first regulation created with the membership of both USGAAP and IFRS, is what motivated this research whose aim is to demonstrate the application of IFRS 15 in construction companies and real estate developers, as well as to emphasize the main changes of regulations applied to this sector. In this regard, methodologically, this study is supported by relevant bibliography and regulatory instruments to the subject, that is, qualitative inductive method. The results show that the regulations proposed by IFRS 15 have greater reliability, transparency, and are more appropriate to the IFRS profile. Thus, it is concluded that, due to the magnitude of the proposed change, companies will have a hard work to adapt, demonstrating the lack of improvement in the applicability of the regulation to the other sectors affected